FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S SELECTED SONGS OF FOLKLORE ALBUM - Kusuma, Dimas; Mahmud, Murni; Affandi, Akhmad (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
“Folklore” is Taylor Swift’s eighth studio album that talks about her personal life, ideal relationship, woman, an inspirational figure, childhood memory and a fiction love story of teenage love triangle. This album consists of 18 songs, and the researcher selects 14 songs to be analyzed. This study aims to analyze the figurative language of the lyrics of the selected songs. The researcher uses a qualitative descriptive method to applied in this study. The researcher analyzes the type and the meaning of the lyrics of the songs. This research produced several findings. There are 29 figurative language that contain in the 14 selected songs which divided into four allegory, two simile, four symbol, two metonymy, two metaphor, three personification, two synecdoche, three hyperbole, one irony, three paradox, one apostrophe, and two litotes. The researcher found that the figurative language is most found in the songs titled “Cardigan” and “Invisible Strings” which has four for each of them and then “Peace” which has three and then The 1, and “The Last Great American Dynasty”, “My Tears Ricochet”, “Seven”, This is Me Trying”, “Illicit Affairs” and “Mad Women” which has two for each of them and then “Exile”, “Mirrorball”, “August” and “Betty” which has one for each of them. In conclusion, this album contains many Figurative Language and used every 12 types of figurative language. There are many meaning of the figurative language in the album, most of them to express feelings and to define something.